Fluor Albus dan Remaja: Efektivitas Edukasi Personal Hygiene di Komunitas Pedesaan - Fauziah, Yaumil; Nasution, Yulia Fatma; Safitri, Yulia (Griya Widya: Journal of Sexual and Reproductive Health, 2025)
Background: Personal hygiene plays a critical role in maintaining the cleanliness of the reproductive organs, particularly among adolescent girls. Lack of awareness and improper hygiene practices can increase the risk of fluor albus (vaginal discharge). Objective: This study aims to assess the effect of health education regarding personal hygiene on the behavioral changes of adolescent girls in preventing fluor albus in Garoga Village, Batangtoru District. Methods: A quasi-experimental design with a one-group pretest-posttest approach was employed. The sample consisted of 30 adolescent girls selected through simple random sampling who met the inclusion criteria. The intervention involved a 4-minute educational video covering the causes, symptoms, and prevention of fluor albus, delivered over a two-week period. Data were analyzed using the Wilcoxon and Mann-Whitney tests. Results: A significant improvement in personal hygiene behavior was observed in the experimental group (p=0.001), while no significant change was noted in the control group (p=0.655). Posttest scores showed a significant difference between the experimental and control groups (p=0.000). Conclusion: Health education using video media is effective in improving personal hygiene behavior among adolescent girls and contributes to the prevention of fluor albus.